Bone Regeneration: Embryonic‐Like Mineralized Extracellular Matrix/Stem Cell Microspheroids as a Bone Graft Substitute (Adv. Healthcare Mater. 19/2018). Issue 19 (10th October 2018) - Fu, Cuicui; Luo, Dan; Yu, Min; Jiang, Nan; Liu, Dawei; He, Danqing; Fu, Yu; Zhang, Ting; Qiao, Yiqiang; Zhou, Yanheng; Liu, Yan
Abstract : In article 1800705, Yanheng Zhou, Yan Liu, and co‐workers, fabricate embryonic‐like mineralized extracellular matrix/stem cell microspheroids (MECS), which provide a physiological microenvironment conducive to intracellular communication and osteogenesis, leading to excellent bone regeneration outcomes. This study demonstrates the feasibility of MECS transplantation as a promising scaffold‐free strategy for cell‐based bone regenerative therapy in tissue engineering.